Effect Of Low Temperature Annealing On Anatase TIO² Layer As Photoanode For Dye-Sensitized Solar Cell - Arith, Faiz; Muhammad Mustafa, Ahmad Nizamuddin; Noorasid, Nur Syamimi; Mohd Abid, Mohd Asyadi Azam; Meriam Suhaimy, Syazwan Hanani; Al-Ani, Oras A.Shareef (Wydawnictwo SIGMA-NOT, 2021)
Dye-Sensitized Solar Cells (DSSCs) have been successfully fabricated with a low annealing temperature (100 °C to 500 °C) approach to the anatase TiO2 photoanode deposited by a screen-printing method. In this paper, the surface morphology and structure of the TiO2 thin films were studied using Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD) and Raman Spectroscope while I-V characteristic was used for the electrical properties. Sample with an annealing temperature of 300 °C displays a good feature in terms of porosity and enhanced agglomerated surface.